2020
DOI: 10.1002/14651858.cd013627
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial mouthwashes (gargling) and nasal sprays administered to patients with suspected or confirmed COVID-19 infection to improve patient outcomes and to protect healthcare workers treating them

Abstract: H. V. (2020). Antimicrobial mouthwashes (gargling) and nasal sprays administered to patients with suspected or confirmed COVID-19 infection to improve patient outcomes and to protect healthcare workers treating them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 17 publications
0
18
0
4
Order By: Relevance
“…Although mouth rinses containing chemical agents (povidone‐iodine, chlorhexidine, cetylpyridinium chloride, oxygen peroxide, essential oils, beta‐cyclodextrin and citrox) are currently used to control SARS‐CoV‐2 load before clinical procedures, scientific proof of their effectiveness is still lacking (Burton et al, 2020; Gottsauner et al, 2020; Herrera et al, 2020; Mendez & Villasanti, 2020; Moosavi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although mouth rinses containing chemical agents (povidone‐iodine, chlorhexidine, cetylpyridinium chloride, oxygen peroxide, essential oils, beta‐cyclodextrin and citrox) are currently used to control SARS‐CoV‐2 load before clinical procedures, scientific proof of their effectiveness is still lacking (Burton et al, 2020; Gottsauner et al, 2020; Herrera et al, 2020; Mendez & Villasanti, 2020; Moosavi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Imran et al 31 suggests that the use of PVP-I has its toxic effects depending on the dose and the contraindications should be evaluated before the prescription. In a review carried out by Burton et al 32 he showed concern about the studies on mouthwashes in progress and does not declare whether he will assess adverse effects or changes in the oral or nasal microbiota.…”
Section: Resultsmentioning
confidence: 99%
“…However, there have been other papers with betadine products that demonstrate that there is no ciliotoxicity of PVP-I products [5,22]. There is also concern that PVP-I may have unknown effects on the microbial flora of the oral cavity [23]. PVP-I showed no deleterious effect on a representative nitrate-reducing species called Veillonella dispar in the oral cavity suggesting it may not have an effect on the normal oral microbial flora [24].…”
Section: Pvp-i (Betadine)mentioning
confidence: 99%
“…We found 17 clinical trials that met our criteria. There is currently a systematic review being done by the Cochrane review of clinical trials for SARS-CoV-2 [23].…”
Section: Clinical Trialsmentioning
confidence: 99%